The Reality of the Strategic Planning of the Faculties and Departments of Physical Education and Sports Sciences According to the Pfeiffer Model - Salam Hantosh Rashed (Journal of Global Pharma Technology, 2016)
The objective of current research is to identify to identify the reality of strategic planning in the faculties and departments of physical education and sport sciences according to the model (Pfeiffer) from the point of view of decision-makers. The research sample included as deans of faculties and heads of departments of physical education in Iraq has been a period of study from 04/03/2017 until 30/05/2017 was used descriptive and analytical approach to address statistical data. The researchers recommended that strategic planning contribute to the success of the college or the department and its development through the interest in choosing decision makers to fill sensitive administrative positions. And the adoption of the results of scientific research and studies that dealt with the subject of strategic planning as a key source for the development of the institution, and activates communication and a lot of it between the leaders and workers to build more bridges of trust between them, through meetings and seminars held continuously.Keywords: Strategic planning, Physical education and Pfeiffer model.